Do daily lead texts help nowcasting GDP growth? - Marc Burri (University of Neuchâtel, Institute of Economic Research (IRENE), 2023)
This paper evaluates whether publicly available daily news lead texts help nowcasting Swiss GDP growth. I collect titles and lead texts from three Swiss newspapers and calculate text-based indicators for various economic concepts. A composite indicator calculated from these indicators is highly correlated with low-frequency macroeconomic data and survey-based indicators. In a pseudo out-of-sample nowcasting exercise for Swiss GDP growth, the indicator outperforms a monthly Swiss business cycle indicator if one month of information is available. Improvements in nowcasting accuracy mainly occur in times of economic distress.
Keywords: C53; E32; E37; 330; Mixed-frequency data; composite leading indicator; news sentiment; recession; natural language processing; nowcasting